(untitled) (AYUSHDHARA, 2019)
Background: In Ayurveda classics Shalakya Tantra is mentioned, among the eight branches of Ayurveda, proves the importance, as well as antiquity of all the diseases arising from eye, ear, nose, throat, oral cavity and Head. Shalakya Tantra bears utmost importance for dealing with the vital sense organs located above the Jatru (clavicle), also considered as the Uttamanga in Ayurveda. To maintain health of a healthy person first and curing the disease of an unhealthy is the principal of Ayurveda. One of the quotations says that prevention is better than cure. We can prevent the diseases by maintaining the life style. According to Ayurveda to maintain a healthy and disease-free life should follow a Dinacharya. Aims: Review Dinacharya modalities (daily regimen) with reference to Shalakya Tantra. Material and Methods: Relevant Ayurveda and modern literature, available information on internet etc. were searched. Discussion: Various Dinacharya modalities gives nourishment to the supra clavicular region and cures ailments of related, also provides preventive and curative benefits. A daily regimen mentioned in Ayurveda classics is a body purification therapy which eradicates toxins and balances Tridosha.